Crowdsourcing e revisão sistemática na área de educação: desenvolvimento de uma plataforma colaborativa de trabalhos sobre formação de professores - Soares Filho, Sidney (2024)
This thesis analyzes and synthesizes the scientific production on Systematic Literature Reviews (SLR) in the field of teacher training, categorizing the studies into relevant themes and promoting accessibility and knowledge sharing through an online collaborative platform. Based on publications indexed in the CAPES Periodicals database and the institutional repositories of UFC and UECE, covering the period from 1967 to 2023, the research identifies critical gaps, trends, and patterns in the literature on teacher education. Using metadata for the organization and categorization of information, as well as meta-analysis to consolidate findings and evaluate methodologies, the research adopts criteria documented in a PRISMA-based flowchart, ensuring transparency and robustness in the process. One of the contributions of this work is the development of a Collaborative Platform for Works on Teacher Training, based on crowdsourcing principles and tools such as Wikiversity, democratizing access to knowledge and encouraging collaboration among researchers and educators. The results highlight the need for more studies on systematic reviews in teacher education due to various factors, including methodological complexity, lack of specific training, focus on primary studies, publication limitations, restricted resources and data access, educational market pressures, undervaluation of synthesis research, and lack of institutional incentives. By contributing to strengthening the dialogue between academia and society, this research advances the understanding of teacher training as a dynamic and multifaceted field, offering pathways to more inclusive and transformative educational practices.